The diagnostic and prognostic value of serum miR-206 in colorectal cancer - Liu, Xingcun (Int J Clin Exp Pathol, 2017)
Circulating microRNAs (miRNAs) are emerging as promising biomarkers for colorectal cancer (CRC). In this study, we sought to examine the diagnostic and prognostic role of serum miR-206 in CRC. A total of 73 CRC cases and 45 healthy control subjects were enrolled in this study. Quantitative reverse transcription PCR (qRT-PCR) was used to measure the relative serum miR-206 levels. Serum miR-206 levels were significantly decreased in CRC patients than normal controls. In addition, serum miR-206 demonstrated good diagnostic performance for discriminating CRC patients from healthy controls. miR-206 levels were increased in the blood samples of CRC patients who received surgery treatment. Moreover, serum miR-206 expression was closely associated with TNM stage and lymph node metastasis. CRC patients with low miR-206 level suffered more unfavorable overall survival and disease free survival compared to those with high miR-206 level. Furthermore, serum miR-206 was confirmed to be an independent prognostic indicator for CRC. In summary, serum miR-206 might be a promising biomarker for the diagnosis and prognosis of CRC.